2017
DOI: 10.1021/jacs.7b01167
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Boronic Acid-Appended Pyridinium Salts and 19F NMR Spectroscopy for Diol Sensing

Abstract: The identification and discrimination of diols is of fundamental importance in medical diagnostics, such as measuring the contents of glucose in the urine of diabetes patients. Diol sensors are often based on fluorophore-appended boronic acids, but these severely lack discriminatory power and their response is one-dimensional. As an alternative strategy, we present the use of fluorinated boronic acid-appended pyridinium salts in combination with F NMR spectroscopy. A pool of 59 (bio)analytes was screened, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…Thev alues of t on and t off were determined by fitting dwell-time histograms for each catechol concentration to single exponential functions.T he forward and reverse rate constants derived from the t values (Table 1) yield an equilibrium association constant of catechol to the boronic acid of K a = 2.4 AE 0.2 10 3 m À1 at 21 AE 1 8 8C( n = 3), consistent with literature values. [5] Short, spike events of varying amplitudes observed in the baseline of single-channel recordings with aP B pore (Supporting Information, Figure S6), which can be seen in addition to the dominant binding events of catechol in Figure 1c,w ere attributed to intrinsic fluctuations within the pore and were neglected during analysis.…”
mentioning
confidence: 99%
“…Thev alues of t on and t off were determined by fitting dwell-time histograms for each catechol concentration to single exponential functions.T he forward and reverse rate constants derived from the t values (Table 1) yield an equilibrium association constant of catechol to the boronic acid of K a = 2.4 AE 0.2 10 3 m À1 at 21 AE 1 8 8C( n = 3), consistent with literature values. [5] Short, spike events of varying amplitudes observed in the baseline of single-channel recordings with aP B pore (Supporting Information, Figure S6), which can be seen in addition to the dominant binding events of catechol in Figure 1c,w ere attributed to intrinsic fluctuations within the pore and were neglected during analysis.…”
mentioning
confidence: 99%
“…The stability (self-healing ability) of phenylboronic ester complex also depends on the conformation of the diol groups in the polymer chains. Schiller et al determined binding constants between phenylboronic acid and different polysaccharides with different diol conformations (Axthelm et al, 2017 ). It was found that phenylboronic acid has a higher affinity for the cis -diol groups than that for the trans -diol groups.…”
Section: Design Strategies For Self-healing Hydrogelsmentioning
confidence: 99%
“…[3] Forexample,boronic acid-containing hydrogels have been used recently for biocompatible continuous glucose monitoring. [4] Despite the growing number of sophisticated boronic acid-based chemosensors that can detect and discriminate sugars, [5] knowledge of the structural interactions between saccharides and boronic acids remains limited.…”
mentioning
confidence: 99%
“…[9] Ther eciprocal of the mean inter-event interval (t on )i s proportional to the catechol concentration, which is consistent with abimolecular interaction for which 1/t on = k on [catechol].I nc ontrast, ap lot of the reciprocal of the mean lifetime of the complex (t off )v ersus the catechol concentration has anear zero slope,which is consistent with au nimolecular dissociation mechanism (1/ t off = k off )( Figure 1d). [5] Short, spike events of varying amplitudes observed in the baseline of single-channel recordings with aP B pore (Supporting Information, Figure S6), which can be seen in addition to the dominant binding events of catechol in Figure 1c,w ere attributed to intrinsic fluctuations within the pore and were neglected during analysis. [5] Short, spike events of varying amplitudes observed in the baseline of single-channel recordings with aP B pore (Supporting Information, Figure S6), which can be seen in addition to the dominant binding events of catechol in Figure 1c,w ere attributed to intrinsic fluctuations within the pore and were neglected during analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation